Pengembangan Media Pembelajaran Interaktif Berbasis Komputer dalam Pembelajaran Matematika, Materi Bilangan pada Kelas 3 SD - Syahroni Syahroni; Maya Nurfitriyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
This study aims to find out how the development of learning media 3D cartoon. The method used Research and Development method (research and development), but more focused on development process using ADDIE method. Stages of development in this research begin by analyzing the needs, designing, creating 3D learning media cartoon after it is applied and then tested the experts. The results showed that the media developed has met the eligible and eligible to be used as a medium of learning 3D cartoon subject matter numbers. This is seen from the results of content validation, and the effectiveness of product by material experts of 94% expressed very well. For languages and communications are easily understood to get 91% percentage, media aspect of 83%, appearance, quality and effectiveness of media by design learning experts of 93% expressed very well. So it can be concluded that 3D learning media cartoon is feasibly used in learning.